Structural Genomic Analysis of SARS-CoV-2 and Other Coronaviruses - Zhang, Qiong; Guo, Huai-Lan; Wang, Jing; Zhang, Yao; Deng, Ping-Ji; Li, Fei-Feng (Frontiers in Genetics, 2022)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the causative agent of the coronavirus disease 2019 (COVID-19) pandemic. In this study, we conducted a comparative analysis of the structural genes of SARS-CoV-2 and other CoVs. We found that the sequence of the E gene was the most evolutionarily conserved across 200 SARS-CoV-2 isolates. The E gene and M gene sequences of SARS-CoV-2 and NC014470 CoV were closely related and fell within the same branch of a phylogenetic tree. The absolute diversity of E gene and M gene sequences of SARS-CoV-2 isolates was similar to that of common CoVs (C-CoVs) infecting other organisms. The absolute diversity of the M gene sequence of the KJ481931 CoV that can infect humans was similar to that of SARS-CoV-2 and C-CoVs infecting other organisms. The M gene sequence of KJ481931 CoV (infecting humans), SARS-CoV-2 and NC014470 CoV (infecting other organisms) were closely related, falling within the same branch of a phylogenetic tree. Patterns of variation and evolutionary characteristics of the N gene and S gene were very similar. These data may be of value for SARS-CoV-2 vaccine development and viral detection.